Perkembangan Transportasi Kereta Api sebagai Penunjang Industri Perkebunan di Keresidenan Lampung 1830-1933 - Oktaviani, Aliza; Mahdi, Sufi Sopan; Rachmedita, Valensy (Historia Madania: Jurnal Ilmu Sejarah, 2024)
Lampung Residency is one of the main export commodity producing areas in the Dutch East Indies. Plantation became the mainstay of Lampung's economy during the colonial period. Pepper, rubber, copra, coffee, and tobacco are commodities that support the development of the economy and trade in Lampung. Over time, the Dutch colonial government continued to make improvements in its colonies, one of which was the improvement of infrastructure such as the construction of railroads to support plantation industry on economic activity and trade in the residency of Lampung 1830-1933. This study looks at the economic policy of the colonial government towards the plantation industry and improving infrastructure in the residency of Lampung as its colony. The methodology used in this study is a historical method using in-depth analysis of source literature. The results showed that the development of plantations in Lampung could not be separated from the various policies and regulations implemented by the Dutch colonial government. The transportation arrangements in the Lampung residency previously contained river routes, such as rivers, but the function of the Tulang Bawang River as a trade transportation route was decreasing along with the construction of the East Sumatran highway and the construction of the Teluk Betung Palembang railway. The construction of the railway line in the residency of Lampung was developed by a railway company named Zuid Sumatra Staatsspoorwegen (ZSS) which connects the railway lines in the South Sumatra and Lampung regions.